Association of the time course of Chinese visceral adiposity index accumulation with cardiovascular events in patients with hypertension - Yuntao Wu; Wenqi Xu; Lu Guo; Wenjuan Li; Lisha Zhang; Lishu Gao; Chenrui Zhu; Shuohua Chen; Liming Lin; Shouling Wu (Lipids in Health and Disease, 2023)
Abstract Background The Chinese visceral adiposity index (CVAI), a simple surrogate measure of visceral fat, is significantly associated with cardiovascular disease (CVD) risk in the general population. This study aimed to evaluate the association of cumulative CVAI (cumCVAI) exposure and its accumulation time course with CVD risk among patients with hypertension. Methods This prospective study involved 15,350 patients with hypertension from the Kailuan Study who were evaluated at least three times in the observation period of 2006 to 2014 (2006–2007, 2010–2011, and 2014–2015) and who were free of myocardial infarction and stroke before 2014. The cumCVAI was calculated as the weighted sum of the mean CVAI for each time interval (value × time). The time course of CVAI accumulation was categorized by splitting the overall accumulation into early (cumCVAI06 − 10) and late (cumCVAI10 − 14) accumulation, or the slope of CVAI versus time from 2006 to 2014 into positive and negative. Results During the 6.59-year follow-up period, 1,184 new-onset CVD events were recorded. After adjusting for confounding variables, the hazard ratios (HRs) and 95% confidence intervals (CIs) for CVD were 1.35 (1.13–1.61) in the highest quartile of cumCVAI, 1.35 (1.14–1.61) in the highest quartile of the time-weighted average CVAI, 1.26 (1.12–1.43) in those with a cumulative burden > 0, and 1.43 (1.14–1.78) for the group with a 10-year exposure duration. When considering the time course of CVAI accumulation, the HR (95% CI) for CVD was 1.33 (1.11–1.59) for early cumCVAI. When considering the combined effect of cumCVAI accumulation and its time course, the HR (95% CI) for CVD was 1.22 (1.03–1.46) for cumCVAI ≥ median with a positive slope. Conclusions In this study, incident CVD risk depended on both long-term high cumCVAI exposure and the duration of high CVAI exposure among patients with hypertension. Early CVAI accumulation resulted in a greater risk increase than later CVAI accumulation, emphasizing the importance of optimal CVAI control in early life.